John Richardson’s Unlikely Narrative of Nationhood: History, the Gothic, and Sport as Prophecy in Wacousta - Buma, Michael (Studies in Canadian Literature, 2011)
In the spirit of seeing Wacousta (1832) as a sort of literary fountainhead, John Richardson’s novel can be read as the unlikely symbolic originator of yet another “Canadian tradition”: the myth of hockey. The seemingly improbable connection between Canada’s “first novel” and its national winter sport rests on two important qualifying claims: first, that Wacousta represents an early gesture toward Canadian multiculturalism and, second, that this reading derives largely from its status as an historical novel. According to Georg Lukács, it is entirely legitimate to read historical fiction as national allegory. Such an interpretive strategy is especially appropriate in the Canadian context in which issues of national identity have been particularly contested and unstable. By placing lacrosse, a formative and symbolic antecedent to modern hockey, at the centre of this thematic and generic trajectory, Richardson inadvertently anticipates the current rhetoric of cultural nationalism that attends Canadian hockey.